Case Study of Exemplary Leadership Practices Impact on New Teacher Integration and School - Chaffin, Megan McLeroy (My University, 2023)
This study aimed to determine how exemplary leadership practices contributed to a collaborative and empowering school culture. The study examined how Kouzes and Posner’s (2017) five practices of exemplary leadership impacted school culture during organizational change which involved the integration of new teachers into the established culture. Building upon prior research concerning organizational theory and culture (Bolman & Deal, 2013; Kouzes & Posner, 2017; Schein, 2010), the study provided evidence to assist in determining if such exemplary leadership practices were critical to ensuring school cultures merged effectively through acceptance, so as to build upon an already recognized positive and productive culture. This study incorporated an embedded single-case study design (Yin, 2018) with myself as the administrator and participant- researcher. It used observations and focus group interviews from teachers in an elementary school in the Southeastern portion of the United States. After thorough data analysis, findings suggested exemplary leadership practices do have an effect on school culture among teachers where a program merger happened; however, more deliberate attention should be made on continuous teacher involvement and feedback in the process. Keywords: leadership, organizational culture, school culture, mergers and acquisitions, change circumstances.
Keywords: Educational leadership; Leadership; Universities and colleges--Mergers; Teachers; Dissertations, Academic--United States